Dystrophin Orchestrates the Epigenetic Profile of Muscle Cells Via miRNAs - Marrone, April K.; Shcherbata, Halyna R. (Frontiers in Genetics, 2011)
Mammalian musculature is a very robust and dynamic tissue that goes through many rounds of degeneration and regeneration in an individual’s lifetime. There is a biological program in place that maintains muscle progenitor cells that, when activated, give rise to intermediate myoblast progeny that consequently differentiate into mature muscle cells. Recent works have provided a picture of the role that microRNAs (miRNAs) play in maintaining aspects of this program. Intriguingly, a subset of these miRNAs is de-regulated in muscular dystrophies (MDs), a group of fatal inherited neuromuscular disorders that are often associated with deficiencies in the Dystrophin (Dys) complex. Apparently, transcriptional expression of many of the muscle specific genes and miRNAs is dependent on chromatin state regulated by the Dys-Syn-nNOS pathway. This puts Dystrophin at the epicenter of a highly regulated program of muscle gene expression in which miRNAs help to coordinate networking between multiple phases of muscle maintenance, degeneration and regeneration. Therefore, understanding the role for miRNAs in physiology of normal and diseased muscle tissue could be useful for future applications in improving the MD therapies and could open new clinical perspectives.